The Urgency of Self-Concept Characteristics in Building High School Students' Learning Motivation: Urgensi Karakteristik Konsep Diri Dalam Membangun Motivasi Belajar Siswa Sekolah Menengah Atas - Janah, Siti Miftahul (Psikologia : Jurnal Psikologi, 2020)
Self-concept is something that must be owned by everyone. The concept of self is not carried from birth, but develops over time and is influenced by the environment. The development of self-concept at every level or age is different, especially in elementary and middle school. The world of education also plays an active role in the development of self-concept, but self-concept also affects education. The development of motivation to learn in a student is related to self-concept, so the characteristics of the self-concept need to be developed according to the age of the student. Moreover, high school students who are classified as adolescents, with characters who want to be recognized and try to find their identity. Self-concept will play a big role in the transitional period between childhood and adulthood. This study used a qualitative descriptive method using research instruments in the form of observation, literature and interviews.